Os impactos e adoção de estratégias no processo logístico em meio a pandemia do Covid-19 - Barros, Rafaella Maduro Machado (Brasil, 2024)
Logistics is a fundamental process in the functioning of the modern world in which we are embedded, dating back to ancient times. It evolves according to external factors and agents in the environment where it operates. The Covid-19 pandemic, which began at the end of 2019, had a significant impact on logistical operations. This was due to disruptions in the functioning of global organizations and an extended period of isolation and social distancing, resulting in the reorganization of supply chains in response to the challenges posed by the pandemic. This research employed a systematic review and narrative review approach with the aim of highlighting the impacts and major changes in logistics during and after the Covid-19 pandemic. At this historical moment, logistics played a crucial role in enabling companies and services to continue operating, maintaining stability and financial transactions even during the restrictions on the movement of people.